المعاملات المالية المحرمة ودورها في إحداث الأزمات المالية المعاصرة - دقاق، محمود عبد الرحمن (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
“The Unlawful Financial Transactions and their Role in the Contemporary Financial Crises: Analytical Study” is a paper which seeks to examine an issue that is very important in our time to raise and highlight. The Study demonstrates the significance of avoiding the unlawful financial transactions in the economic system, for such transactions play a role in creating financial crises, given the established policy of globalization, in its negative sense, and the lots of people being deluded by the financial boom that has been brought by the positive system, without considering consequent detriments. This paper provides an elucidation of the Islamic law approach concerning financial transactions and the extent of its actuality and viability. Does it constitute a valid alternative to the unlawful transactions adopted by positive systems? What effect does it have on individuals, society and state? The researcher has employed the inductive approach in tracing the scientific material and collecting it from the classical and contemporary sources. He has also adopted the analytical descriptive approach in considering the fundamental concepts that make up the study components, and conceptualizing the relationship with each other, such as financial crisis concept and rules of prohibition, alongside clarification of the link between the two of them, from the Sharia perspective. The researcher has come to conclusion that the contemporary financial crisis has emerged due to five reasons: interest-based loans, debt factoring, commercial insurance, derivatives and short-term mortgage loans. His study clarifies that the unlawful financial transactions rest upon five bases: usury, risk and uncertainty, fraud, prohibited items trading, and monopoly. Ultimately, this paper demonstrates that what causes financial crises is largely connected with the rules of prohibition, that is, there is a great wisdom behind such prohibition. Moreover, in order to be able to stave off any other financial crisis, it is necessary to effect a complete cessation of unlawful transactions and find valid alternatives.